Speed and agility training in female soccer players - A systematic review - Stankovic, M.; Djordjevic, D.; Katanic, B.; Petrovic, A.; Jelaska, I.; Bjelica, D.; Mekic, A. (SportMont, 2023)
Female soccer players performs between 1350-1650 activity changes, along with jumping, accelerating and decelerating. The ability to repeat these actions identically in competition are essential for success in female soccer. Hence, the study aim was to summarize relevant literature on the effects of speed and agility training in female soccer players. Literature identification were conducted according to the PRISMA guidelines and in multiple databases (Google Scholar, PubMed, Scopus, Cochrane Library, ProQuest, EBSCOhost and Science Direct). Based on the pre-defined inclusion criteria (year of publication (2003-2022), full-text study published in English, the experimental study that had included healthy and injury-free female soccer players as participant sample) database search have identified 23502 potential studies. In the end, a total of seven full-text studies were included, with a total of 165 female participants. There were a variety of experimental programs, such as resisted, assisted and traditional sprint training, high-speed treadmill, speed and agility trainings, and repeated agility and strength group, along with their comparison with strength training group. Likewise, different types of duration, intensity and frequency were observed and resulted overall speed and agility improvements in female soccer players. Authors can conclude that only with well prepared and organized program, especially in pre-season, female soccer players should be able to improve important and specific factors, in order to achieve desired aim and result in terms of speed and agility.